MEKANISME PENINJAUAN MASA KERJA PEGAWAI NEGERI SIPIL GURU (STUDI DI WILAYAH KERJA KANTOR REGIONAL I BADAN KEPEGAWAIAN NEGARA YOGYAKARTA) - Mohamad Nur Ramandhanu Nugroho; Annisa Istrianty (RECHTSTAAT, 2014)
Tenure review of the Civil Service is used to adjust the work experience has been in the travel by a civil servant before the Civil Service into the Civil Service remains. The purpose of this study is to provide a descriptive understanding of the implementation of the Teacher Tenure Review in the working area of the State Personnel Board Regional Office 1 Yogyakarta. Data collection techniques used in this research is to use library research and field studies. The more the State Civil Servants recruitment profession Teachers in Central Java and Yogyakarta is increasing, which most of them have to work first as a temporary employee in the State agencies or as private employees. Therefore, the Civil Service submitted a reconsideration of its work in order to get the additional work that would improve the working class, the working class when the time increases, also will increase the salaries of civil servants so that the level of income they also increased. The cause delays implementation Teacher Tenure Review in the working area Regional Office of State Personnel Board 1 Yogyakarta due to the discovery of the files are still incomplete and the discovery of a fictitious files in the file that required for Tenure Review process.. Keywords: State Personnel Board, review of Tenure, Civil Servants, Teachers.